Breaking industrial relations’ stalemate at ABC Ltd.: a strategic rapprochement - Niharika Gaan (Vilakshan (XIMB Journal of Management))
Purpose – On 12th June 2015, a strike by contract workers was declared at Rampur terminal, All India Business in oil corporation (ABC) Ltd. The strike had disrupted the normal services of the terminal. Under such circumstances, Mr Ravi Sharma (Head human resources of the eastern region, ABC Ltd.) was unable to decide how to save the company from such a disorderly situation without any increased loss of production and manpower cost liabilities. Could Mr Ravi Sharma resolve the issue of strike through an approach of strategic rapprochement when the disruptions made by workers and local miscreants went out of control? Design/methodology/approach – In-depth interview in the year 2019 was conducted with the protagonist Mr Ravi Sharma and the trade union members at the regional office of ABC Ltd., Kolkata and Rampur Terminal, respectively, to convert the narratives in the form of a fictitious case study. Four rounds of interviews were conducted by the author to complete the data collection procedure. The company™s-related information was sourced through a secondary database furnished by company™s officials. However, the data about the company, the key characters and other recognizable information have been disguised to preserve the confidentiality of information. Findings – The strike was called by the contract workers at Rampur terminal for two primary reasons, namely, wage increase and giving preference to local people for employment whether regular or contract. Mr Ravi Sharma could pacify the unforeseen situation by adopting two-pronged strategies, namely, first, he could successfully gain the confidence of the union leader and secondly, set the environment for the conciliation proceeding so that agreement settled will not be failed to be implemented. Originality/value – The case uses a system perspective of Industrial relation proposed by Dunlop (1958) to highlight the interplay between employer, government and trade unions influenced by politics and mafia that determine eventually the industrial peace in the organization.